Pengaruh Kondisi Temperatur Pirolisis Tandan Kosong Kelapa Sawit Terhadap Komposisi Produk Tar - Nury, Dennis Farina; Luthfi, Muhammad Zulfikar; Zullaikah, Siti (REACTOR: Journal of Research on Chemistry and Engineering, 2022)
Oil palm empty fruit bunch (EFB) is one of the biomass wastes that have a great potential of a bioenergy resource due to its natural properties, such as high calorific value. The conversion of EFB biomass into valuable biofuels can achieved through biochemical and thermochemical processes. Tar (bio oil), the liquid product from the pyrolysis is one of the most attractive biofuels. The study aims to determine the effect of temperature process of pyrolysis EFB on its tar production under droptube reactor. The results showed that maximum tar yield was 43,80% obtained at 500 °C. The EFB tar produced at 500 °C was also determined to have a higher of phenol compound at 51,9%. The high phenolic content indicates its potential to be used for the production of renewable phenolic resins. Hence, the present work of pyrolysis of EFB presents itself as a promising method to produce phenol rich tar (bio-oil) from biomass waste.